Deslocações afluentes para o direito de cidadania à proteção social distributiva no Sistema Único de Assistência Social - Costa, Raquel Cristina Serranoni da (2024)
The importunation of the question "has social assistance acquired settlement as a public policy of citizenship right?" is the fuel of the thesis that runs through the affluent displacement in historical time, with a keen eye to identify how the rights manifests itself and which expressions are permanent of charitable and philanthropic practices in the Unified System of Social Assistance - SUAS. The hypothesis is that the constitutionality of the social assistance policy of citizenship right, crosses, in historical time, displacement of conflicting affluences, between expressions of charity and philanthropy and manifestations of law. This is present in the implementation of SUAS. The thesis, based on observation, directed by meticulous scientific curiosity, indicates that the policy of social assistance as a right of citizenship, faces embarrassment to, in SUAS, constitute unity in its operation. There are two highlighted questions: the first lies in the conceptual conception/ interpretation that results in the operationalization of services and benefits and is based on the question: how far is it absorbed that social assistance policy is a right of citizenship? The second issue is to consider that, if in fact it is a single management system, SUAS would have to rely on an organization and processes of services and benefits that allow it to operate with its three functions: protect, monitor and defend, ensuring its secured securities. The object is relations established in the real field of SUAS attentions, which are informed by notions given by the interpretation of social assistance policy and its distributive social protection productions. The plot of the thesis is a conceptual construction, from the categorization by similarities, what their interlocutors capture and how they mean social assistance and SUAS, raw material that will make it possible to find answers to the so unsettling question. The research is inductive qualitative and uses the following techniques: academic and documentary analytical reading; semi-structured interviews; narratives and material produced in collectives with the population using a CRAS in a large city in São Paulo. The guiding questions of the central question intuited thematic groupings that are dealt with in 3 chapters exploring notions and expressions of citizenship and, charity and philanthropy in three successive perspectives of approximation of the real with conceptual foundations: first, the scenario in the municipalities of the consolidation of the social assistance policy and its unique system; second, the historical exploitation of the social assistance policy in search of a conception in its political and ethical direction as a right of citizenship and, third, the exploration of notions about charity and citizenship in the search for a conceptualization that links the meanings and signifiers of the scope of the research, which requires historical, theoretical and social analysis